2019
DOI: 10.1111/pere.12289
|View full text |Cite
|
Sign up to set email alerts
|

Romantic competence behavior during problem solving among emerging adult dating couples: Development of an observational coding system

Abstract: This study examined the hypothesis that romantic competence (RC) skills would be demonstrated behaviorally during dating couple problem solving interactions. A coding system was developed for RC behavior, and its validity was examined through its association with relationship satisfaction and negative affect expressed. A total of 106 emerging adult dating couples in different‐sex relationships were assessed using the Romantic Competence Interview for Emerging Adults, and they participated in a dyadic problem‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…However, consistent with prior research (Davila et al, 2017a; Zhou & Davila, 2019), and prior data reported from this sample (Davila et al, 2017b) there was a significant positive association between relationship satisfaction and romantic competence. Given that research to date, including this study, is cross-sectional, it will be important to examine temporal associations, as well the role of behavior in those associations.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, consistent with prior research (Davila et al, 2017a; Zhou & Davila, 2019), and prior data reported from this sample (Davila et al, 2017b) there was a significant positive association between relationship satisfaction and romantic competence. Given that research to date, including this study, is cross-sectional, it will be important to examine temporal associations, as well the role of behavior in those associations.…”
Section: Discussionsupporting
confidence: 90%
“…The current study examined the association between romantic competence and couple support behaviors among emerging adults. As we have noted elsewhere (Davila et al, 2017a, 2017b; Zhou & Davila, 2019), emerging adults are an important group in which to study relational processes. They are trying to determine what type of relationship/partner is right for them (Arnett, 2000; Scott et al, 2009).…”
Section: The Current Studymentioning
confidence: 83%
See 2 more Smart Citations
“…Moreover, it is important to develop interventions not only for ADA prevention, but also programs aimed at promoting relational well‐being more broadly. For example, Davila and colleagues have examined the construct of romantic competence, a skills‐based model of adaptive romantic relationship functioning, which has been shown to be associated with important indicators of healthy romantic functioning among adolescents and emerging adults (Cuccì et al, 2020; Davila et al, 2009; Davila, Mattanah, et al, 2017; Davila, Wodarczyk, & Bhatia, 2017; Zhou & Davila, 2019). In addition, one study (Davila et al, 2020) has demonstrated preliminary support for the efficacy of a relationship education workshop designed to teach romantic competence skills to emerging adults.…”
Section: Discussionmentioning
confidence: 99%